FASHION TAG: CYCLICALITY AND SUSTAINABILITY AND THEIR IMPORTANCE IN PRODUCT COMMUNICATION - de Mello, Alessandra Mamim (Seven Editora, 2026)
"The fashion industry has demonstrated a growing concern for sustainable causes, driving a search for production processes that minimize environmental damage. This study presents the systematization of a family business that reinvented itself by migrating to the fashion industry, adopting the fashion tag as its primary product to engage customers. The main objective is to address production methods and sequences, aiming to understand and improve the pillars of sustainability and cyclicality in tag development, from conception to disposal. Consequently, the life cycle of the tag’s raw material is understood as a final product that returns to the industry in a safe and recyclable manner. This process enhances the understanding of the social, economic, and environmental impact of this movement within the global fashion scenario. "